Global patterns and drivers of coniferous leaf-litter decomposition in streams and rivers - Xiang, Hongyong; Li, Kun; Cao, Lina; Zhang, Zhenxing; Yang, Haijun (Frontiers in Ecology and Evolution, 2022)
Many streams and rivers are heterotrophic ecosystems that are highly depend on cross-ecosystem subsidies such as leaf-litter (LL). Terrestrial LL can be consumed by macroinvertebrates and microbes to fuel the detrital-based food webs in freshwaters. To date, our knowledge of LL decomposition in freshwaters is largely biased on broadleaved LL, while the patterns and drivers of coniferous leaf-litter (CLL) decomposition in streams and rivers remain poorly understood. Here, we present a global investigation of CLL decomposition in streams and rivers by collecting data from 35 publications. We compared LL breakdown rates in this study with other global-scale studies (included conifers and broadleaved species), between evergreen and deciduous conifers, and between native and invasive conifers. We also investigated the climatic, geographic (latitude and altitude), stream physiochemical characteristics, and experimental factors (e.g., mesh size and experimental duration) in influencing CLL decomposition. We found that: (1) LL breakdown rates in this study were 18.5-28.8% and 4.9-16.8% slower than other global-scale studies when expressed as per day and per degree day, respectively. Conifer LL in coarse-mesh bags, for evergreen and invasive conifers decomposed 13.6%, 10.3%, and 10.8% faster than in fine-mesh bags, for deciduous and native conifers, respectively; (2) CLL traits, stream physiochemical characteristics, and experimental factors explained higher variations in CLL decomposition than climatic and geographic factors; (3) CLL nutritional quality (N and P), water temperature, and experimental duration were better predictors of CLL decomposition than other predictors in categories of LL traits, stream physiochemical characteristics, and experimental factors, respectively; and (4) total and microbial-mediated CLL breakdown rates showed linear relationships with latitude, altitude, mean annual temperature, and mean annual precipitation. Our results imply that the replacement of native forests by conifer plantation would impose great impacts on adjacent freshwaters by retarding LL processing rate. Moreover, future climate warming which is very likely to happen in mid and high latitude areas according to the IPCC 6th report would accelerate LL decomposition, with potential consequence on food depletion for detritivores in freshwaters during hot summers.